2016
DOI: 10.1016/j.jaci.2015.11.037
|View full text |Cite
|
Sign up to set email alerts
|

The cardiomyocyte protein αT-catenin contributes to asthma through regulating pulmonary vein inflammation

Abstract: Background Recent genome-wide association studies have identified single nucleotide polymorphisms in the protein αT-catenin (αT-cat; CTNNA3) that correlate with both steroid-resistant atopic asthma and asthmatic exacerbations. α-catenins are important mediators of cell-cell adhesion and αT-cat is predominantly expressed in cardiomyocytes. In the lung, αT-cat appears exclusively expressed in the cardiomyocytes surrounding pulmonary veins, but its contribution to atopic asthma remains unknown. Objective To und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Our in vivo findings provide direct evidence for a protective role of miR‐218‐5p‐CTNND2 pathway in eosinophilic airway inflammation in asthma. It was reported that CTNNA3 (encoding αT‐catenin) plays an important role in asthma airway inflammation because CTNNA3 knockout mice manifested attenuated AHR and airway inflammation after allergen challenge . Although CTNNA3 expression was reported to be predominantly in cardiomyocytes surrounding pulmonary veins, we demonstrated that CTNNA3 transcripts were increased in asthma bronchial brushings and IL‐13‐stimulated HBE cells.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Our in vivo findings provide direct evidence for a protective role of miR‐218‐5p‐CTNND2 pathway in eosinophilic airway inflammation in asthma. It was reported that CTNNA3 (encoding αT‐catenin) plays an important role in asthma airway inflammation because CTNNA3 knockout mice manifested attenuated AHR and airway inflammation after allergen challenge . Although CTNNA3 expression was reported to be predominantly in cardiomyocytes surrounding pulmonary veins, we demonstrated that CTNNA3 transcripts were increased in asthma bronchial brushings and IL‐13‐stimulated HBE cells.…”
Section: Discussionmentioning
confidence: 54%
“…We found that CTNND2 (encoding δ‐catenin) was one of the candidate targets. Since CTNNA3 plays a role in asthma airway inflammation, we next focused on the role of CTNND2 in asthma. miRNA regulates gene expression via acting on the 3′‐UTR of the mRNA.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations